Outcomes of Patellar Replacement Vs Patellar Neurectomy in Total Knee Replacement - Usman Zafar Dar, Mohammad Nauman Shahid, Ali Muqaddas, Sameer Ahmed, Muhammad Ahmed, Naeem Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the outcomes of patellar replacement and patellar neurectomy in Patients undergoing Total Knee Replacement . Materials & Methods: The design of this study was a cross sectional study design and this study was conducted in DHQ Teaching Hospital Gujranwala. Total 30 Patients were enrolled in this study and they were divided into two groups. Group A constitutes of 15 Patients underwent Post tibial neurectomy. And Group B consisting of 15 Patients went through Tibial Resection. All the patients have been assessed through the Tinel test on the painful area and self-administered Patient-Reported Outcome Measurements (PROMs): Patellar replacement also known as patellofemoral arthroplasty, is a surgical procedure that is performed in conjunction with total knee replacement (TKR) to relieve pain in the knee joint caused by patellofemoral arthritis or other conditions affecting the patella. All the patients of Group B were given anesthesia to numb the area. An incision was made in front of the knee to expose the patella and surrounding structures. Removal of the patella: The patella was carefully removed from the knee joint. The underside of the patella was reshaped to fit a prosthetic component that was implanted in its place. The patellar component was attached to the reshaped surface of the patella using bone cement. The patella was repositioned in the knee joint and attached to the femur using sutures. The incision was closed using sutures or staples. The goal of patellar replacement is to reduce pain and improve function in the knee joint. All the group A participants went through Patellar neurectomy. Patellar neurectomy is a surgical procedure that involves cutting or removing the nerve endings that supply sensation to the patella. Results: Total 30 Patients participated in this study. In Group A =15 Patients who underwent patellar Neurectomy and 15 Patients in Group B who experienced Tibia Resection. Total 5 months follow up was done. Group B participants showed excellent Results. NRS score decreased to 0 in Group B. While in patellar Neurectomy group A two patients experienced still moderate pain, Remaining 13 patients although did not experienced pain but felt numbness on limbs. Practical Implication: Patellar neurectomy involves cutting or removing the nerve endings that supply sensation to the patella, interrupting the transmission of pain signals from the patella to the brain. Although it is less time consuming but can cause numbness or altered sensation in the skin over the patella, which may affect the patient’s quality of life Does not address underlying patellar instability or misalignment, which can still cause pain and functional limitations Can be associated with a risk of complications such as neuroma, infection, stiffness. Conclusion: Patellar Resection with TKA has better outcomes than Patellar Neurectomy. Patellar denervation with electrocautery is effective in reducing pain and opioid consumption after total knee replacement. Postoperative range of motion is significantly better in patellar denervation group, which means that patellar denervation significantly improves clinical outcome Keywords: Total Knee Replacement, Patellar Replacement, Neurectomy, Neurectomy, Tibia Resection, Pain, Prosthesis